PANDUAN PEMBUATAN KOMIK UNTUK MAHASISWA SENI RUPA DAN DESAIN DALAM MENINGKATKAN KETERAMPILAN KREATIF DAN TEKNIS - Arifin, Irfan; Nurjayanti, Nurjayanti; Satriadi, Satriadi; Alimuddin, Alimuddin (Universitas Negeri makassar, 2024)
This study aims to develop a comic creation guide specifically designed for art and design students to enhance their creative and technical skills. Comics, as a medium of expression integrating visual and narrative elements, offer significant potential for dynamically conveying ideas. However, students often face challenges in creating structured and communicative comics due to the lack of guides relevant to academic needs. This research employs a research and development (R&D) method with a project-based approach. The guide is designed to encompass the stages of pre-production, production, and post-production, integrating theory and practice. Product validation shows that 85% of students found the guide helpful in understanding the comic creation process comprehensively, while 90% stated that the visualizations in the guide facilitated their understanding of the material. The research output, a Comic Creation Guidebook, is expected to serve as an effective reference for art and design education and contribute to the literature on visual arts education.